2022
DOI: 10.31234/osf.io/z82tf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cross-Cultural Variation in Cooperation: A Meta-Analysis

Abstract: Impersonal cooperation among strangers enables societies to create valuable public goods, such as infrastructure, public services, and democracy. Several factors have been proposed to explain variation in impersonal cooperation across societies, referring to institutions (e.g., rule of law), religion (e.g., belief in God as a third-party punisher), cultural beliefs (e.g., trust) and values (e.g., collectivism), and ecology (e.g., relational mobility). We tested 17 pre-registered hypotheses in a meta-analysis o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 116 publications
(188 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, the study samples were mostly college students, and college demographics have changed in the United States over the past several decades, to include more women and minorities (Anderson, 2003; Becker et al, 2010). That said, prior research has not found that cooperation varies by gender (Balliet et al, 2011; Spadaro, Jin, et al, 2022) or according to ethnicity in the United States (meta-analytic summary provided in the CoDa; Spadaro et al, in press). In addition, we found no significant difference in cooperation between student and nonstudent samples, and that the overall pattern of an increase of cooperation over time did not change when controlling for student sample (see the ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study samples were mostly college students, and college demographics have changed in the United States over the past several decades, to include more women and minorities (Anderson, 2003; Becker et al, 2010). That said, prior research has not found that cooperation varies by gender (Balliet et al, 2011; Spadaro, Jin, et al, 2022) or according to ethnicity in the United States (meta-analytic summary provided in the CoDa; Spadaro et al, in press). In addition, we found no significant difference in cooperation between student and nonstudent samples, and that the overall pattern of an increase of cooperation over time did not change when controlling for student sample (see the ).…”
Section: Discussionmentioning
confidence: 99%